PERMASALAHAN YANG DIHADAPI GURU SD INP 12/79 BIRU 1 DALAM PELATIHAN PADA SAAT MENGAWALI PENGGUNAAN APLIKASI UNTUK MENENTUKAN TINGKAT KESUKARAN SOAL DAN CARA MENGATASINYA - Sudarto, Sudarto; Muliadi, Muliadi; Rukayah, Rukayah; Sitti Jauhar; Firdaus, Firdaus (Bajang Institute, 2025)
Participants in this activity were the teachers at SD INP 12/79 BIRU 1 in Tanete Riattang District, Bone Regency. The problem in this activity was that teachers experienced problems or difficulties in starting to use the application to determine the level of difficulty of sums. To address this problem, mentoring was provided by providing direct guidance to the participants on how to start using the application to determine the level of difficulty of sums. Data collection techniques included observation and questionnaires. Results and Conclusions: The problems or difficulties experienced by teachers in starting or beginning to use the application to determine the level of difficulty of sumss included the following aspects: writing the answer key in the application menu provided, saving the files, reading processed data regarding the level of difficulty of questions already in the application, opening the saved files, adding the sums to the